High‐Entropy Halides for Intercalation Battery Electrode Materials - Sebastian Schumacher; Dr. Evgeny V. Alekseev; Dr. Shicheng Yu; Dr. Hermann Tempel; Prof. Dr. Rüdiger‐A. Eichel (ChemElectroChem)
Abstract The potential use of high‐entropy materials in batteries has recently attracted considerable interest. Compared to traditional materials, high‐entropy materials exhibit a high defect density and degree of internal entropy, resulting in enhanced ion storage capabilities, ionic conductivity, and electrochemical stability. High‐entropy oxides represent a more extensively investigated material for various electrochemical applications, particularly for potential use as a cathode or electrolyte in battery applications. These multicomponent systems are distinguished by their structural complexity and exhibit enhanced cycling stability, exceeding the performance of traditional oxide materials. The exploration of high‐entropy halides as electrode materials is less extensive than that of their traditional counterparts, despite the latter being the subject of considerable research. This work offers a concise overview of how high‐entropy materials can be applied to halide phases, focusing on the transition from high‐entropy oxides to high‐entropy halides.